Glaciological Research in the Canadian Arctic - Baird, P.D. (ARCTIC, 1955)
The "glacierized" highland rim of the Eastern Arctic extends north for 1,600 miles from southern Baffin Island to northernmost Ellesmere. Ice forms include glacier caps, highland, transection, valley, cirque, and piedmont glaciers, and shelf ice on the north coast of Ellesmere. Incidental ice observations prior to, and glaciological work after 1945 are reviewed, and some results given of the latter: Baffin Island Expeditions of the Arctic Institute in 1950 to the Clyde area and Barnes Icecap; in 1953 to Penny Highland Icecap on Cumberland Peninsula; Ellesmere Ice Shelf Expeditions of Hattersley-Smith and others in 1953 and 1954; and investigations by J. Mercer on Grinnell and Terra Nivea Icecaps in southern Baffin, 1952 and 1953. General appearance and budgetary state of Canadian Arctic glaciers are noted, with suggestions of future glaciological, geomorphological, and bathymetrical problems.